Two new species of Araniella (Aranei: Araneidae) from Western Himalaya, with notes on species reported from India - Alireza Zamani; Yuri Marusik (K M K Scientific Press Ltd., 2025)
Araniella Chamberlin et Ivie, 1942 from India is surveyed. As a result, two new species, A. levii sp.n. and A. maasdorpi sp.n., are described on the basis of male specimens from high altitudes of Himachal Pradesh and Uttarakhand, northern India, and a new combination is established for Araniella nympha (Simon, 1889), comb.n. (ex. Araneus). Comments are provided for three other species known from this country.